KASUS PEMBUNUHAN PASUTRI DI JATIBENING BEKASI - Felicia Kristi; Faza Adelia; Heskya Elfania; Anis Nurfaizah; Fannisa 'Azzabillah; Abriel Moza (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Murder is a crime against life that has serious implications for public security and law enforcement. This study aims to analyze the criminal law aspects of the murder case involving a married couple in Jatibening, Bekasi, by examining the elements of the crime, the investigation process, the causative factors, and the criminal liability of the perpetrator. The study employs a normative juridical method using statutory and case approaches. Research data were collected through library research based on legislation, scientific journals, criminal law textbooks, and other relevant documents. The findings indicate that the perpetrator's actions fulfilled the elements of murder as stipulated in Article 338 of the Indonesian Criminal Code and may also be subject to Article 365 paragraph (4) due to the existence of robbery accompanied by violence resulting in the victim's death. Economic motives were identified as the primary cause of the crime, while the investigation process involved witness examinations, crime scene investigations, and evidence collection. The study concludes that the proper application of criminal law is essential to ensure legal certainty, justice, and the protection of citizens' right to life.